Revision of the enigmatic South African Cryptolaryngini (Coleoptera, Curculionidae), with description of a new genus and twenty-two new species - (:unkn) unknown (My University, 2023)
The weevil genus Cryptolarynx Van Schalkwyk, 1966 is endemic to the Northern and Western Cape provinces of South Africa. The two previously known species of the genus, C. vitis (Marshall, 1957) andC. estriatus (Marshall, 1957), have an aberrant globular body and head shape, which has made it difficult to place the genus into the classification systems of the Curculionoidea. This paper presents the description of 21 new species of Cryptolarynx from South Africa (C. subglaber Haran sp. nov., C. squamulatus Haran sp. nov., C. muellerae Haran sp. nov., C. hirtulus Haran sp. nov., C. robustus Haran sp. nov., C. namaquanus Haran sp. nov., C. carinatus Haran sp. nov., C. variabilis Haran sp. nov., C. pyrophilus Haran sp. nov., C. pilipes Haran sp. nov., C. armatus Haran sp. nov., C. falciformis Haran sp. nov., C. oberprieleri Haran sp. nov., C. spinicornis Haran sp. nov., C. cederbergensis Haran sp. nov., C. homaroides Haran sp. nov., C. marshalli Haran sp. nov., C. endroedyi Haran sp. nov., C. oberlanderi Haran sp. nov., C. san Haran sp. nov., and C. luteipennis Haran sp. nov.) and of one new genus and species, Hadrocryptolarynx major Haran gen. et sp. nov., also from South Africa. A redescription of the European Journal of Taxonomy 877: 1–89 (2023) 2 genus Cryptolarynx is provided to incorporate the characters of the new species. The plant genus Oxalis (Oxalidaceae) is recorded as larval host for several species of Cryptolarynx and for Hadrocryptolarynx Haran gen. nov., as their larvae develop in the subterranean bulbs of members of the genus, and the egg, larva and pupa of C. variabilis are described. The characters of the Cryptolarynx larva confirm that Cryptolaryngini are an early-diverging group of Curculionidae, with a placement among taxa currently classified in the subfamily Brachycerinae sensu lato, and although their exact taxonomic position remains unresolved, some larval characters, and also pupal ones, suggest a close rel
Keywords: African Research